Accuracy of Four Tooth Size Prediction Methods on Malay Population. (14th November 2012) - Mahmoud, Belal Khaled; Abu Asab, Saifeddin Hamed I.; Taib, Haslina
Abstract : Objective . To examine the accuracy of Moyers 50%, Tanaka and Johnston, Ling and Wong and Jaroontham and Godfrey methods in predicting the mesio-distal crown width of the permanent canines and premolars (C + P 1 + P 2 ) in Malay population. Materials and Methods . The study models of 240 Malay children (120 males and 120 females) aged 14 to 18 years, all free of any signs of dental pathology or anomalies, were measured using a digital caliper accurate to 0.01 mm. The predicted widths (C + P 1 + P 2 ) in both arches derived from the tested prediction equations were compared with the actual measured widths. Results . Moyers and Tanaka and Johnston methods showed significant difference between the actual and predicted widths of (C + P 1 + P 2 ) for both sexes. Ling and Wong method also showed statistically significant difference for males, however, there was no significant difference for females. Jaroontham and Godfrey method showed statistical significant difference for females, but the male values did not show any significant difference. Conclusion . For male Malay, the method proposed by Jaroontham and Godfrey for male Thai proved to be highly accurate. For female Malay, the method proposed by Ling and Wong for southern Chinese females proved to be highly accurate.